Anomalous Price Behavior Around Repurchase Tender Offers - LAKONISHOK, JOSEF; VERMAELEN, THEO (Journal of Finance, 1990)
ABSTRACT This paper reports anomalous price behavior around repurchase tender offers. Buying shares before the expiration date of a repurchase tender offer and tendering to the firm produces, on average, abnormal returns of more than 9 percent over a period shorter than one week. In addition, we find that repurchasing companies experience economically and statistically significant abnormal returns in the two years after the repurchase. The upward price drift is mainly caused by the behavior of the small firms in the sample.